Oral Health Knowledge of Periodontal Disease among University Students - Bader K. Al-Zarea (International Journal of Dentistry)
Objectives. The aim of this study was to evaluate levels of oral health knowledge of periodontal disease among nondental university students. Materials and Methods. Two hundred and fifty university students (mean age 20.1 years ± 2.5) were recruited into this study. The participants completed a structured questionnaire during a personal interview. The questionnaire consisted of items to assess participants’ personal data (age, gender, level of study, and specialty) and oral heath knowledge related to periodontal disease. Statistical significance was based on probability values of less than 0.05. Results. Participants showed poor knowledge of causes, signs, symptoms, and preventive measures of gum disease. The level of study had no relationship with students’ knowledge of the initiating factors of periodontal disease (P<0.05), but had a significant relationship with the knowledge of periodontal disease’s signs, preventive measures, and relations to general health and systemic disease (P<0.05). Students from scientific disciplines had more knowledge of periodontal disease’s causes, preventive measures, and relations to general health and systemic disease (P<0.05) than those from humanity disciplines. Conclusions. There were significant differences in oral health knowledge regarding periodontal disease between students from different levels of studies and different disciplines.